Citizen adoption of E-government services: a systematic literature review with weight and meta-analysis - Ahmed Saleh, Rakib (Insight Society, 2024)
This study investigates the determinants influencing citizens’ intentions to embrace and use e-government services in developing countries. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, known for their rigorous and systematic approach, are employed to examine the fundamental attributes, provide extensive descriptive statistics, synthesize the elements, use analytical tools, and present the results from the selected quantitative papers. A weighted meta-analysis was performed on forty-three quantitative research articles on e-government adoption, encompassing 401 relationships, and published in journals within the last ten years. All the participants are from the Asian and African continents. The findings suggest that perceived trust, perceived quality, performance expectancy, effort expectancy, social influence, self-efficacy, and facilitating conditions are the most crucial factors of behavioral intention via the mediation effects of attitude and perceived satisfaction. Furthermore, several demographic characteristics, such as age, gender, education, and experience with e-government services, moderate the association between the mediators and behavioral intention. Thus, we propose a new citizen-centric model named the Integrated Model of E-government Adoption (IMEGA), designed to address the current research gap and predict the extent to which citizens in developing countries would accept e-government services. This paper examines the implications of the findings for both theoretical frameworks and practical applications. Furthermore, the limits of the current study are acknowledged, and future research directions have been provided.